Organisational culture and ethnic diversity in nursing homes: a qualitative study of healthcare workers' and ward nurses' experiences - Jonas Debesay; Sanjana Arora; Marit Fougner (BMC, 2022)
Abstract Background The increase in care needs that comes with an ageing population, in combination with a shortage of healthcare workers, has made ethnic diversity among healthcare workers (HCW) an evident reality across many countries. This article aims to explore how a multicultural workplace is experienced, through the accounts of HCWs and leaders in nursing homes. Methods This article reports on the findings from qualitative interviews with 16 HCWs and managers from nursing homes in Oslo. The interviews were conducted from August to September 2021. We analysed the data using a reflective thematic analysis informed by a hermeneutic-phenomenological approach. Results Six themes emerged from the interview data: (1) understanding diversity through shared norms and multicultural experiences, (2) greater flexibility in a multicultural workforce, (3) challenging traditional norms in a multicultural workforce, (4) language proficiency and exclusionary practices at work, (5) perceptions of the role of the ward nurse, and (6) prejudices among and harassment from patients. Conclusions To ensure the effective organisation and wellbeing of HCWs in a multicultural workforce, managers must develop an inclusive organisational culture. They must be able to engage with difficult topics and conflicts that may arise in the working environment.